Biological Functions of Plasma Membrane-Derived Extracellular Vesicles and Their Role in Diseases - Antwi-Baffour, Samuel; Kyeremeh, Ransford; Martin-Odoom, Alexander; Seidu, Mahmood A; Ayeh-Kumi, Patrick F (Journal of Cells, 2015)
Plasma Membrane-derived Extracellular Vesicles (PMEVs) are membrane-coated vesicles of diameter 0.1 to 1.5µm, carrying various proteins inherent in their parental cells. PMEVs are released when cells undergo activation/apoptosis via blebbing and shedding and have a function in intercellular communication. Exposition of phosphatidylserine (PS) on the outer membrane leaflet that mark them as a biologically distinct entity could also explain a role for PMEVs in phagocytosis and thrombosis. The purpose of this review is to outline and discuss some of the functions of PMEVs in detail to throw more light on its biological effects as more research delve into emerging therapies targeting the microvesicle communication system. The role of PMEVs as a differentiation agent and therefore its possible use in differentiation therapy is discussed. In some experiments, the myeloid differentiating agents all trans retinoic acid (ATRA), phorbol 12-myristate 13-acetate (PMA) and histamine, which inhibit promonocyte proliferation, induced an intracellular Ca2+-mediated PMEV release from HL-60 promonocytes. These PMEVs caused HL-60 cells to enter G0/G1 cell cycle arrest and induce terminal monocyte-to-macrophage differentiation through TGF-β1 mediation. The review also discusses the relationship between PMEVs and diseases where it is known that patients with certain inflammatory diseases show increased PMEV levels in the plasma. The review conclude on the fact that PMEVs have a lot of biological functions that are beneficial to the physiological functions in humans and therefore more work is required to elucidate their composition and the mechanisms involved in exertion of their effects.